Strengthening Harmonious Islam Through a Philological Approach - Defri Ramadani; Manswab Mahsen Abdulrahman (Program Pascasarjana UIN Sumatera Utara Medan, 2025)
Indonesia possesses an extensive cultural heritage, one of the most valuable forms of which is its collection of ancient manuscripts. These manuscripts preserve historical, religious, legal, literary, and cultural knowledge that reflects the intellectual development of the Indonesian archipelago, particularly the spread and evolution of Islam Nusantara. However, many of these manuscripts are currently threatened by physical deterioration, inadequate preservation, and limited scholarly attention. This study aims to examine the scope of Nusantara manuscripts, explain the concept and significance of the philological approach, and describe the procedures of philological research in preserving and interpreting ancient texts. This research employs a qualitative method through observation, interviews, and literature review to analyze manuscript preservation practices and relevant archival regulations. The findings reveal that Nusantara manuscripts, written in various local languages and scripts such as Malay, Javanese, Pegon, and Arabic, constitute an invaluable source of knowledge covering religion, history, law, politics, medicine, customs, and other disciplines. Philology plays a crucial role in restoring, transliterating, authenticating, and interpreting these manuscripts to ensure their textual accuracy and historical reliability. Furthermore, philological studies contribute significantly to safeguarding Indonesia's cultural heritage, strengthening the identity of Islam Nusantara, and providing reliable primary sources for interdisciplinary research in history, law, sociology, anthropology, and religious studies. Therefore, the philological approach is indispensable not only for manuscript preservation but also for promoting a deeper understanding of Indonesia's rich intellectual and cultural traditions.